2015
DOI: 10.1128/cvi.00170-15
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Suppresses the Function of Lung Dendritic Cells via Caveolin-1

Abstract: Caveolin-1 (Cav-1), the principal structural protein of caveolae, has been implicated as a regulator of virus-host interactions. Several viruses exploit caveolae to facilitate viral infections. However, the roles of Cav-1 in herpes simplex virus 1 (HSV-1) infection have not fully been elucidated. Here, we report that Cav-1 downregulates the expression of inducible nitric oxide synthase (iNOS) and the production of nitric oxide (NO) in dendritic cells (DCs) during HSV-1 infection. As a result, Cav-1 deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Furthermore, HSV-2 can limit DC presentation of viral antigens on MHC-I molecules by interfering with the transport of antigenic peptides from the cytoplasm to the endoplasmic reticulum and decrease the expression of T cell costimulatory molecules on the DC surface, thus impeding effective T cell activation (Figure 1 ) ( 74 , 75 , 77 , 78 ). HSV can also block the activity of inducible nitric oxide synthase (iNOS) and NO production, by interacting with caveolin-1 (Cav-1) in DCs (Figure 1 ) ( 79 ). Additionally, and most importantly, HSV-2 elicits DC apoptosis early after infection, further limiting the chances of the host to establish an optimal antiviral T cell response (Figure 1 ) ( 17 , 78 , 80 ).…”
Section: Dendritic Cell Infection With Hsv-2mentioning
confidence: 99%
“…Furthermore, HSV-2 can limit DC presentation of viral antigens on MHC-I molecules by interfering with the transport of antigenic peptides from the cytoplasm to the endoplasmic reticulum and decrease the expression of T cell costimulatory molecules on the DC surface, thus impeding effective T cell activation (Figure 1 ) ( 74 , 75 , 77 , 78 ). HSV can also block the activity of inducible nitric oxide synthase (iNOS) and NO production, by interacting with caveolin-1 (Cav-1) in DCs (Figure 1 ) ( 79 ). Additionally, and most importantly, HSV-2 elicits DC apoptosis early after infection, further limiting the chances of the host to establish an optimal antiviral T cell response (Figure 1 ) ( 17 , 78 , 80 ).…”
Section: Dendritic Cell Infection With Hsv-2mentioning
confidence: 99%
“…This is important because Src-mediated signaling induced by JEV is known to play a critical role in neuronal cell death. Earlier studies revealed the role of lipid rafts in the activation of Src, Ras, Raf, ERK, and NF-кB, which all contribute to JEV-induced TNF-α and IL-1β production (McCubrey et al 2007;Wu et al 2015). Furthermore, involvement of lipid rafts in Src-mediated signaling pathways upstream of the activation of Raf/ ERK/NF-кB has been reported in response to several stimuli (Roux and Blenis 2004).…”
Section: Blue Tongue Virusmentioning
confidence: 99%
“…Further study of infected DCs has revealed that the transfer of antigen from the cytosol to the endoplasmic reticulum is blocked by HSV infection, which could downregulate antigen presentation to T cells by DCs through restricting the binding of antigen to the major histocompatibility complex 1 (MHC‐1) molecule in cells . The data have also suggested that HSV is capable of interacting with caveolin‐1 to alter the activity of nitric oxide synthase and limit the production of NO and that the migration rate of infected DCs moving from the local tissue to the lymph nodes was decreased because of an increased death rate . All of these data suggest the hypothesis that by interfering with DCs, a major antigen‐presenting cell in the immune system, HSV infection might lead to abnormal immune signaling in T cells and induce weakened adaptive immunity.…”
Section: The Strategy By Which Hsv Evades Monitoring By the Immune Symentioning
confidence: 99%